Decreased free water clearance is associated with worse respiratory outcomes in premature infants. - Tuomo Vuohelainen; Riitta Ojala; Anita Virtanen; Päivi Korhonen; Tiina Luukkaala; Päivi Holm; Outi Tammela (PLoS ONE, 2011)
OBJECTIVE: The goal was to elucidate predictors of decreased free water clearance (DFWC) in very low birth weight (VLBW) infants. We hypothesized that DFWC and fluid retention are linked to the severity of pulmonary problems and prolonged respiratory support, especially to nCPAP treatment. METHODS: The investigation was carried out at Tampere University Hospital between 2001 and 2006. The study population comprised 74 VLBW infants born at 29.21 (24.57-34.14) weeks of gestation. Median birth weight was 1175 (575-1490) grams. We measured plasma and urine osmolality and 24-hour urine volume to calculate free water clearance (FWC) for each infant. If FWC was less than 30 ml/kg/day the infant was classified as having DFWC. RESULTS: There were 38 (51.4%) infants with DFWC in the study population. The median duration of the observed DFT period was 14 (4-44) days. The gestational age at birth was lower for DFWC infants compared to infants with normal FWC (NFWC), 28.29 (24.57-32.86) vs. 30.00 (25.57-34.14) weeks (p = 0.001). DFWC infants also needed longer ventilator treatment, 2 (0-23) vs. 0.50 (0-23) days (p = 0.046), nCPAP treatment 30 (0-100) vs. 3 (0-41) days (p<0.0001) and longer oxygen supplementation 47 (0-163) vs. 22 (0-74) days (p = 0.011) than NFWC infants. All values presented here are medians with ranges. CONCLUSIONS: DFWC appears to be frequently connected with exacerbation and prolongation of pulmonary problems in VLBW infants. Cautious fluid administration seems to be indicated in VLBW infants with prolonged respiratory problems and DFWC.